Implementation of The People's Business Credit Program on The Welfare of Micro, Small, and Medium Enterprises in Bengkulu City - Alfharobby, Wahyu; Anggi Josetio Prayoga (EDU PARTNER INDONESIA, 2024)
The challenges in implementing the policy on village fund utilization priorities are often complex and vary between villages, including resource limitations and external factors such as the COVID-19 pandemic. This research aims to analyze the implementation of the Decree of the Minister of Village, Development of Disadvantaged Regions, and Transmigration Number 11 of 2020 regarding the Priority of Village Fund Utilization in Urak Village, Makalti Tama Sub-District, Rahat District. The policy aims to maximize benefits for rural communities by improving quality of life and welfare, reducing poverty, and enhancing public services. This qualitative research focuses on aspects such as adequacy of implementation, day-to-day operations, efficiency, and effectiveness, with information gathered through interviews. The study indicates that the ministerial policy has not been fully implemented. Only three out of four focus areas have been executed: improving quality of life, increasing welfare, and poverty alleviation. The public service development program has not been implemented. The prioritization of the first three areas is due to the socio-economic conditions of the community. External factors such as the reduction of the state budget due to the COVID-19 pandemic have also affected the implementation of this policy. This study suggests a comprehensive evaluation of village budget priorities, considering the local context and the need for proactive measures to respond to severe situations like the pandemic. Permasalahan dalam implementasi kebijakan prioritas penggunaan dana desa seringkali kompleks dan bervariasi antar desa, termasuk keterbatasan sumber daya dan pengaruh faktor eksternal seperti pandemi COVID-19. Penelitian ini bertujuan untuk menganalisis implementasi Keputusan Menteri Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi Nomor 11 Tahun 2020 tentang Prioritas Penggunaan Dana Desa di Desa Urak, Kecamatan Makalti Tama, Kabupaten Rahat. Kebijakan ini bertujuan memaksimalkan manfaat bagi masyarakat desa melalui peningkatan kualitas hidup, kesejahteraan, pengurangan kemiskinan, dan peningkatan pelayanan publik. Penelitian kualitatif ini fokus pada aspek kecukupan pelaksanaan, operasional sehari-hari, efisiensi, dan efektivitas, dengan informasi dikumpulkan melalui wawancara. Hasil penelitian menunjukkan kebijakan belum sepenuhnya dilaksanakan. Dari empat fokus area, hanya tiga yang dijalankan: peningkatan kualitas hidup, kesejahteraan, dan pengentasan kemiskinan. Program pengembangan pelayanan publik belum diimplementasikan. Prioritas pada tiga area pertama disebabkan oleh kondisi sosial ekonomi masyarakat. Faktor eksternal seperti pengurangan anggaran akibat pandemi COVID-19 turut mempengaruhi implementasi kebijakan ini. Studi ini menyarankan evaluasi komprehensif terhadap prioritas anggaran desa dengan mempertimbangkan konteks lokal serta kebutuhan langkah-langkah proaktif dalam menghadapi situasi serius seperti pandemi.